Ethno-sustainability of an Indigenous Architecture in the Northern Philippines Using Grounded Theory - Tabao, Michael; Tablan, Junar P (Alanya Üniversitesi, 2025)
This study investigates the ethno-sustainability of Itawit architecture as a distinctive indigenous practice in the Cagayan province of Northern Philippines. Employing a qualitative grounded theory approach, data were gathered through ethnographic interviews, field observations, and archival research with building owners, carpenters, shamans, and elders from Middle and Southern Cagayan. Using coding, memoing, and thematic analysis, the research thematised vernacular construction practices and knowledge systems, framing them as integral components of cultural heritage and community resilience. Findings demonstrate that Itawit architecture embodies sustainable principles through locally sourced materials, ritual practices, and collective labour systems such as ivvet (community construction). Despite modernisation pressures and the adoption of permanent materials, traditional ecological knowledge and oral transmission continue to sustain building practices and cultural identity. The study highlights “ethno-sustainability” as a framework wherein spiritual beliefs, environmental sensitivity, and social contracts interconnect to preserve community resilience. Documentation of terms, visual records, and rituals provides a baseline reference for conservationists, policymakers, and urban planners. Integrating these indigenous practices into contemporary planning contributes to culturally inclusive and environmentally sustainable development in the Philippines and beyond.